2015
DOI: 10.1007/s11914-015-0292-x
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic and Probiotic Regulation of Bone Health: Role of the Intestine and its Microbiome

Abstract: Recent advances in our understanding of how the intestinal microbiome contributes to health and disease have generated great interest in developing strategies for modulating the abundance of microbes and/or their activity to improve overall human health and prevent pathologies such as osteoporosis. Bone is an organ that the gut has long been known to regulate through absorption of calcium, the key bone mineral. However, it is clear that modulation of the gut and its microbiome can affect bone density and stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
134
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(141 citation statements)
references
References 76 publications
(105 reference statements)
3
134
0
4
Order By: Relevance
“…Consistent with this, Sjogren et al found that bacterial colonization of young adult GF animals resulted in loss of trabecular bone mass and an increase in bone-resorbing osteoclasts (13). However, other studies have suggested that treatment with beneficial microbes modestly increases bone mineral density (21)(22)(23)(24)(25)(26) and protects against bone loss after sex steroid deficiency (27). Discrepant results in studies examining the effect of microbiota on bone may reflect differences in the composition of the resident microbiota, age of the animal at colonization and necropsy, mouse strain, and sex.…”
mentioning
confidence: 87%
“…Consistent with this, Sjogren et al found that bacterial colonization of young adult GF animals resulted in loss of trabecular bone mass and an increase in bone-resorbing osteoclasts (13). However, other studies have suggested that treatment with beneficial microbes modestly increases bone mineral density (21)(22)(23)(24)(25)(26) and protects against bone loss after sex steroid deficiency (27). Discrepant results in studies examining the effect of microbiota on bone may reflect differences in the composition of the resident microbiota, age of the animal at colonization and necropsy, mouse strain, and sex.…”
mentioning
confidence: 87%
“…Nevertheless, carrageenan-induced paw edema was not affected by the isolated harpagoside constituent. This signifies that harpagoside may not have an anti-inflammatory effect, at least in the dosage used in this study [70,71]. This suggests that other HP constituents may be responsible for the anti-inflammatory effect.…”
Section: Harpagophytum Procumbens Fam Pedaliaceaementioning
confidence: 79%
“…Importantly, dried plum is rich in soluble and insoluble fibers, including pectin, fructans, hemicelluloses, and cellulose [23,40], which are known to increase mineral absorption (e.g., calcium) [71]. For instance, fibers are fermented by colonic bacteria, resulting in the production of short-chain fatty acids (SCFA).…”
Section: Mdpimentioning
confidence: 99%
“…Exposure of weaning mice to antibiotics increases bone mass (15), suggesting that alteration of the normal microbiota may, in fact, recapitulate the beneficial skeletal actions of a germ-free environment. An alternative strategy in lieu of antibiotics would be to use probioticslive microorganisms that provide health benefits to the host (16). Probiotics have been long known to increase bone strength in chickens (17) and to improve eggshell hardness (16).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy in lieu of antibiotics would be to use probioticslive microorganisms that provide health benefits to the host (16). Probiotics have been long known to increase bone strength in chickens (17) and to improve eggshell hardness (16). Several other notable observations underscore the premise that altering the microbiota using probiotics can alter bone remodeling and/or bone mass in hypogonadal states.…”
Section: Discussionmentioning
confidence: 99%